Characterizing the trophic niches of stocked and resident cyprinid fishes: consistency in partitioning over time, space and body sizes. Issue 14 (26th June 2016) - Bašić, Tea; Britton, J. Robert
Abstract: Hatchery‐reared fish are commonly stocked into freshwaters to enhance recreational angling. As these fishes are often of high trophic position and attain relatively large sizes, they potentially interact with functionally similar resident fishes and modify food‐web structure. Hatchery‐reared barbel Barbus barbus are frequently stocked to enhance riverine cyprinid fish communities in Europe; these fish can survive for over 20 years and exceed 8 kg. Here, their trophic consequences for resident fish communities were tested using cohabitation studies, mainly involving chub Squalius cephalus, a similarly large‐bodied, omnivorous and long‐lived species. These studies were completed over three spatial scales: pond mesocosms, two streams and three lowland rivers, and used stable isotope analysis. Experiments in mesocosms over 100 days revealed rapid formation of dietary specializations and discrete trophic niches in juvenile B. barbus and S. cephalus . This niche partitioning between the species was also apparent in the streams over 2 years. In the lowland rivers, where fish were mature individuals within established populations, this pattern was also generally apparent in fishes of much larger body sizes. Thus, the stocking of these hatchery‐reared fish only incurred minor consequences for the trophic ecology of resident fish, with strong patterns of trophic niche partitioning and diet specialization. Application of these results to decision‐making frameworks should enable managers to make objective decisions on whether cyprinid fish should be stocked into lowland rivers according to ecological risk. Abstract : As hatchery‐reared fish are commonly stocked into freshwaters to enhance recreational angling, we tested the trophic interactions between stocked European barbel Barbus barbus with resident fishes. Across a range of temporal and spatial scales and body sizes, strong patterns of trophic niche partitioning were apparent. These results indicate that stocked B. barbus are unlikely to incur major ecological consequences in recipient freshwater ecosystems.